Database systems : design, implementation, and management - Coronel, Carlos; Morris, Steven (Stamford, Connecticut : Cengage Learning Asia Pte Ltd, 2015)
Practical and easy to understand, DATABASE SYSTEMS: DESIGN, IMPLEMENTATION, AND MANAGEMENT, Eleventh Edition, gives students a solid foundation in database design and implementation. Filled with visual aids such as diagrams, illustrations, and tables, this market-leading text provides in-depth coverage of database design, demonstrating that the key to successful database implementation is in proper design of databases to fit within a larger strategic view of the data environment. Renowned for its clear, straightforward writing style, this text provides students with an outstanding balance of theory and practice. The eleventh edition has been updated to include expanded relational algebra coverage, updated business vignettes showing the impact of database tech in the real world, updated coverage of cloud data services, expanded coverage of Big Data and related Hadoop technologies, SQL coverage expanded to include MySQL databases, and many other improvements! In addition, new review questions, problem sets, and cases have been added throughout the book so that students have multiple opportunities to test their understanding and develop real and useful design skills.
Part I: Data concepts. Database Systems -- Data Models -- Part II: Design concepts. The Relational Database Model -- Entity Relationship (ER) Modeling -- Advanced Data Modeling -- Normalization of Database Tables -- Part III: Advanced design and implementation. Introduction to Structured Query Language (SQL) -- Advanced SQL -- Database Design -- Part IV: Advanced database concepts. Transaction Management and Concurrency Control -- Database Performance Tuning and Query Optimization -- Distributed Database Management Systems --Business Intelligence and Data Warehouses -- Part V: Databases and the internet. Database Connectivity and Web Technologies -- Part VI: Database administration. Database Administration and Security.
Includes bibliographical references and index.
Keywords: DATABASES